Exploring the Impact of the Counseling Service on Student-Teachers’ Academic Performance: The Case of E.P. College of Education, Bimbilla (International Journal of Scientific Research and Management (IJSRM), 2020)
The study sought to explore the impact of counseling service on students’ academic performance in E.P. College of Education, Bimbilla. The objectives of the study were: one, to examine the impact of the counselling service on student-teachers’ academic performance; two, to find out what motivates student-teachers to patronize the counseling service; and lastly, to find out the perception student-teachers have about the role of the counseling service in E.P. College of Education, Bimbilla. The study employed the qualitative approach with case study in focus. Two hundred and fifty (250) student-teachers, four (4) tutor-counselors and a vice principal were selected using the stratified sampling technique. The respondents were made to fill questionnaires and also interviewed. After successful data collection, the data was analyzed using SPSS version 17. The data was also analyzed using descriptive statistics such as frequency distributions and percentages. Qualitative descriptions were also used in the presentation of data. The study found out that counselling service equips student-teachers with good study and time management skills to improve their academic performance. The study concluded that counseling service could help student-teachers build positive self-image which could lead to better academic performance. One of the implications of the findings is that if student-teachers seek counseling, they would be assisted to develop good study skills.